Spatial microbiome-metabolic crosstalk drives CD8+ T-cell exhaustion through the butyrate-HDAC axis in colorectal cancer - Chen, Xiaoyang; Zhang, Yinxu; Zhang, Guangyu; Wang, Dai; Dou, Linhua; Wang, Yuxi; Huang, Zining; Liu, Xiaomei (Frontiers in Microbiology, 2025)
BackgroundThe spatial organization of intratumoral microbiota and its metabolic impact on immunotherapy response in colorectal cancer (CRC) is unclear, limiting targeted interventions.MethodsWe integrated single-cell RNA-seq, spatial transcriptomics, and microbial multi-omics from a discovery cohort of 23 treatment-naïve CRC patients. Findings were validated in an independent validation cohort from The Cancer Genome Atlas (TCGA-CRC, n = 159).ResultsSpatial depletion of Streptococcus and Acetivibrio in tumor niches disrupts butyrate-histone deacetylase (HDAC) signaling, leading to programmed cell death 1 (PDCD1) hyperacetylation and CD8+ T-cell exhaustion. The Colorectal Cancer Microbiome Score (CMS) may serve as a predictive biomarker for immunotherapy response and HDAC inhibitor-based combination therapy. We developed the CMS, a spatial biomarker that stratifies patients by microbial-metabolic dysfunction, predicting immunotherapy resistance (e.g., higher tumor immune dysfunction and exclusion (TIDE) scores; p < 0.01) and guiding combinatorial HDAC inhibition for CMS-defined subgroups. In silico fecal microbiota transplantation (FMT) validated CMS as an actionable target for microbiota modulation. Butyrate supplementation in vitro restored HDAC activity and reduced PD-1 expression on CD8+ T cells, validating the proposed mechanism.ConclusionOur study unveils a spatially defined, microbiome-driven metabolic niche that epigenetically programs CD8+ T-cell exhaustion via the butyrate-HDAC axis, revealing a targetable mechanism to overcome immunotherapy resistance in CRC.